2012
DOI: 10.1111/j.1365-294x.2011.05464.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly similar microbial communities are shared among related and trophically similar ant species

Abstract: Ants dominate many terrestrial ecosystems, yet we know little about their nutritional physiology and ecology. While traditionally viewed as predators and scavengers, recent isotopic studies revealed that many dominant ant species are functional herbivores. As with other insects with nitrogen-poor diets, it is hypothesized that these ants rely on symbiotic bacteria for nutritional supplementation. In this study, we used cloning and 16S sequencing to further characterize the bacterial flora of several herbivorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
210
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(246 citation statements)
references
References 75 publications
20
210
4
Order By: Relevance
“…These symbionts are protected by a proventricular filter (Lanan et al, 2016), remain stable in laboratory-reared colonies and likely coevolved with their hosts (Sanders et al, 2014). 'Verrucomicrobia' belonging to the order Opitutales are consistently detected at high numbers in the ant midgut (Anderson et al, 2012;Hu et al, 2014;Lanan et al, 2016). As such, these vastly abundant Opitutales symbionts may play important contributory roles in host nutrition and disease resistance (Dillon & Dillon, 2004).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These symbionts are protected by a proventricular filter (Lanan et al, 2016), remain stable in laboratory-reared colonies and likely coevolved with their hosts (Sanders et al, 2014). 'Verrucomicrobia' belonging to the order Opitutales are consistently detected at high numbers in the ant midgut (Anderson et al, 2012;Hu et al, 2014;Lanan et al, 2016). As such, these vastly abundant Opitutales symbionts may play important contributory roles in host nutrition and disease resistance (Dillon & Dillon, 2004).…”
mentioning
confidence: 99%
“…By using PCR amplification and DNA sequencing techniques, previous studies have shown that members of the 'Verrucomicrobia' constitute part of a stable, autochthonous community of symbionts maintained in the guts of Cephalotes 'turtle' ants (Anderson et al, 2012;Kautz et al, 2013;Russell et al, 2009). These symbionts are protected by a proventricular filter (Lanan et al, 2016), remain stable in laboratory-reared colonies and likely coevolved with their hosts (Sanders et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using PCR amplification and DNA sequencing techniques have revealed that Cephalotes ants harbor a core gut microbiota (Anderson et al, 2012;Hu et al, 2014;Kautz et al, 2013;Russell et al, 2009). Bacteria in this core microbiota consistently include members of the Burkholderiales, Rhizobiales, Xanthomonadales, Opitutales and Pseudomonadales phylotypes (Anderson et al, 2012;Hu et al, 2014;Russell et al, 2009), signifying their importance as stable, autochthonous members of the gut community (Hu et al, 2014;Sanders et al, 2014).…”
mentioning
confidence: 99%
“…Studies using PCR amplification and DNA sequencing techniques have revealed that Cephalotes ants harbor a core gut microbiota (Anderson et al, 2012;Hu et al, 2014;Kautz et al, 2013;Russell et al, 2009). Bacteria in this core microbiota consistently include members of the Burkholderiales, Rhizobiales, Xanthomonadales, Opitutales and Pseudomonadales phylotypes (Anderson et al, 2012;Hu et al, 2014;Russell et al, 2009), signifying their importance as stable, autochthonous members of the gut community (Hu et al, 2014;Sanders et al, 2014). These symbionts are likely to have coevolved with their hosts over their evolutionary history (Sanders et al, 2014), and, as shown for symbionts in the termite (Brune & Ohkuma, 2011;Wertz et al, 2012;Wertz & Breznak, 2007b) and honeybee gut (Engel et al, 2012;Engel & Moran, 2013;Kwong & Moran, 2013), likely confer beneficial functions to host nutrition and disease resistance (Dillon & Dillon, 2004).…”
mentioning
confidence: 99%